2015
DOI: 10.1016/j.febslet.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor 1α down regulates cell surface expression of α1,2‐fucosylated glycans in human pancreatic adenocarcinoma cells

Abstract: Edited by Veli-Pekka LehtoKeywords: Glycosyltransferase Regulation of gene expression Fucosyltransferase Hypoxia inducible factor 1 a (HIF-1a) Cancer a b s t r a c tThe a1,2-fucosyltransferase activity in pancreatic tumors is much lower compared to normal pancreatic tissue. Here we show that hypoxia inducible factor (HIF) 1a is constitutively expressed in the pancreatic cancer cell lines Pa-Tu-8988S and Pa-Tu-8988T and suppresses the expression of the a1,2-fucosyltransferase genes FUT1 and FUT2. Down regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…A study demonstrated that HIF-1α negatively regulated the fucosyltranferase expression (FUT1 and FUT2) in pancreatic cancer cell lines, resulting in low expression of fucosylated glycans on the cell surface [84]. These enzymes catalyze the addition of fucose to the galactose residues in Galβ1–3GlcNAc-R and Galβ1-4GlcNAc-R glycans to produce H type 1 and 2 antigens, respectively, precursor structures of the Blood Group A and B antigens.…”
Section: Hypoxia Regulates Glycosyltransferases Glycosidases and Nucmentioning
confidence: 99%
See 4 more Smart Citations
“…A study demonstrated that HIF-1α negatively regulated the fucosyltranferase expression (FUT1 and FUT2) in pancreatic cancer cell lines, resulting in low expression of fucosylated glycans on the cell surface [84]. These enzymes catalyze the addition of fucose to the galactose residues in Galβ1–3GlcNAc-R and Galβ1-4GlcNAc-R glycans to produce H type 1 and 2 antigens, respectively, precursor structures of the Blood Group A and B antigens.…”
Section: Hypoxia Regulates Glycosyltransferases Glycosidases and Nucmentioning
confidence: 99%
“…These enzymes catalyze the addition of fucose to the galactose residues in Galβ1–3GlcNAc-R and Galβ1-4GlcNAc-R glycans to produce H type 1 and 2 antigens, respectively, precursor structures of the Blood Group A and B antigens. The reduction of α1,2-fucosylation results in low H-antigen levels, and, thereafter, in low levels of BG antigens, which has been associated with increased cellular motility and resistance to apoptosis [84]. However, prostate cells (RWPE1) cultured in acute hypoxia demonstrated significant upregulation of FUT1, GCNT2, and GCNT3 (Polylactosamine Branching N-Acetylglucosaminyltransferases 2 and 3), which are required for prostate cancer lipid antigen (PCLA) synthesis [69].…”
Section: Hypoxia Regulates Glycosyltransferases Glycosidases and Nucmentioning
confidence: 99%
See 3 more Smart Citations